2019
DOI: 10.21776/ub.apmba.2019.008.01.4
|View full text |Cite
|
Sign up to set email alerts
|

Green Marketing and Intention to Mantain Sustainable : Case Study On Rural Tourism In Malang

Abstract: The negative impact of aggressive marketing on tourism destinations in Indonesia become a main concern to various groups. Whereas, the purpose of developing rural tourism is not only to achieve economic sustainability but also to sustain the environment. The concept of green marketing is estimated to be a worthy solution to maintain the sustainability of the tourism destination. Therefore, this study aims to determine the effect of green marketing concepts to affect tourists' intention for avoiding the damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…There is a big impact of green development carried out by tourism city managers on tourist destinations to follow the carrying capacity of tourist cities, and there is a big impact of real evidence in tourist cities on tourist destinations to keep up with the management of tourist cities (Cahyanti & Iliyawati, 2018). Green Promoting affects tourist destinations to keep up with the state travel industry (Cahyanti & Menanti, 2019). Beramas, in his article entitled "Reasonable Examination of the Travel Industry in the Tanjung Setia Tourism Area of the West Coast Regime," revealed that the implementation of supporting aspects of the travel industry in the tourist area of Tanjung Setia has not been carried out by these three points of view.…”
Section: Previous Researchmentioning
confidence: 99%
“…There is a big impact of green development carried out by tourism city managers on tourist destinations to follow the carrying capacity of tourist cities, and there is a big impact of real evidence in tourist cities on tourist destinations to keep up with the management of tourist cities (Cahyanti & Iliyawati, 2018). Green Promoting affects tourist destinations to keep up with the state travel industry (Cahyanti & Menanti, 2019). Beramas, in his article entitled "Reasonable Examination of the Travel Industry in the Tanjung Setia Tourism Area of the West Coast Regime," revealed that the implementation of supporting aspects of the travel industry in the tourist area of Tanjung Setia has not been carried out by these three points of view.…”
Section: Previous Researchmentioning
confidence: 99%